Pelatihan Peningkatan Kompetensi Guru melalui Integrasi AI dalam Pembelajaran di SMP Negeri 1 Kota Ambon - Dewilna Helmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The use of artificial intelligence (AI) in education holds significant potential to enhance the quality of learning and the effectiveness of teaching. This study aims to evaluate a teacher competency development program through the integration of AI, particularly in the development of AI-based teaching materials utilizing the Kelas Ajaib feature in the Canva application. The training involved 40 teachers from SMP Negeri 1 Kota Ambon and was conducted through workshops and interactive simulations. Evaluation results indicated an 85% level of participant enthusiasm and 86% satisfaction, reflecting a highly positive response to the program. However, teacher competence in creating AI-based instructional media reached only 75%, suggesting a need for further mentoring and improved supporting infrastructure. The main challenges identified included limited hardware availability and difficulties in adapting to new technologies. Therefore, follow-up training, enhanced technical support, and improved school facilities are recommended. Collaboration among educational stakeholders is essential to ensure the sustainability of AI integration in the learning process. Further research is recommended to examine the long-term impact of AI implementation on teaching quality and student engagement.